Phosphoproteomic analysis reveals the diversity of signaling behind ErbB‐inhibitor‐induced phenotypes - Vaparanta, Katri; Song, Zejia; Farahani, Iman; Jokilammi, Anne; Merilahti, Johannes; Örling, Johanna; Virtanen, Noora; Haapaniemi, Pekka; Sahlgren, Cecilia; Elenius, Klaus; Paatero, Ilkka (Wiley-Blackwell, 2026)
The impact of kinase inhibitors on the phosphoproteome has been rarely investigated at a whole-organism level. Here, we performed a phosphoproteomic analysis in embryonic zebrafish to identify the signaling pathways perturbed by ErbB receptor tyrosine-protein kinase inhibitors gefitinib, lapatinib, and AG1478 at the organism level. The phosphorylation of proteins associated with the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt), p38 mitogen-activated protein kinase (MAPK), Notch, Hippo/Yap, and β-catenin signaling pathways was differentially regulated by the ErbB inhibitors. Gene set enrichment analyses indicated differential neurological and myocardial phenotypes of different ErbB inhibitors. To assess the neurological and myocardial effects, motility and ventricle growth assays were performed with inhibitor-treated embryos. The treatment with the inhibitors targeting the PI3K/Akt, p38 MAPK, and Notch signaling pathways, along with the ErbB inhibitors AG1478 and lapatinib, perturbed the overall movement and ventricle wall growth of zebrafish embryos. Taken together, these results indicate that inhibitors with overlapping primary targets can affect different signaling pathways while eliciting similar physiological phenotypes.